URGENSI DAN KONTRIBUSI SOSIOLINGUISTIK DALAM LINGUISTIK EDUKASIONAL - Hasanah, Mamluatul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2007)
Language learning deals with the concept of language truth, language teaching, language teacher, and language context. Sociolinguistics is one of the applied linguistics which answers to the questions of language in society and also language context. Thus, sociolinguistics has great contribution on language learning especially relating with the language policy and the choise of appropriate text-book which is suitable with the social context of language learner.